In vivo cancer targeting via glycopolyester nanoparticle mediated metabolic cell labeling followed by click reaction. (October 2019) - Wang, Hua; Bo, Yang; Liu, Yang; Xu, Ming; Cai, Kaimin; Wang, Ruibo; Cheng, Jianjun
Abstract: We developed glycopolyesters (GPs) via azido-sugar initiated ring-opening polymerization of O -carboxyanhydrides (OCAs) and achieved efficient in vivo cancer targeting via GP-nanoparticle (GP-NP) mediated metabolic cell labeling followed by Click reaction. GP-NP shows controlled release of azido-sugars and can efficiently label LS174T colon cancer cells with azido groups in tumor-bearing mice. The exogenously introduced azido groups render excellent in vivo cancer targeting and retention of dibenzocyclooctyne-Cy5 (DBCO-Cy5) with an increasing tumor retention enhancement over time (68% at 6 h, 105% at 24 h, and 191% at 48 h) compared to control mice without azido labeling. The tumor accumulation of DBCO-doxorubicin is also significantly enhanced in GP-NP pretreated mice, resulting in improved in vivo anticancer efficacy. This study, for the first time, proposes the use of azido-sugar initiated polymerization of OCAs to form sugar delivery vehicles with high stability and controlled release, and demonstrates the increasing tumor targeting effect of DBCO-cargo over time by azido-modified tumor cells. Graphical abstract: Efficient cancel labelling with azido groups was attained by treating mice with azido-sugar conjugated glycopolyester nanoparticles; significantly enhanced targeting and retention of DBCO-cargo in cancer tissues was achieved. Image 1